A Predictive Model of High-Risk Sexual Behaviors in Female High School Students Based on Cognitive Emotion Regulation Styles with the Mediating Role of Hardiness - Alizadeh Godarzi, Mahbobeh; Pirkhaefi, Alireza; Haghighat, Sara (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to develop and test a predictive model of high-risk sexual behaviors among female high school students based on cognitive emotion regulation strategies, with psychological hardiness as a mediating variable.Methods and Materials: The study employed an applied, descriptive-correlational design using structural equation modeling. The sample included 300 female students from second-cycle high schools in Babol city during the 2022–2023 academic year, selected via non-random, voluntary sampling. Data were collected using standardized questionnaires: the Sexual Risk Behaviors Questionnaire, the Cognitive Emotion Regulation Questionnaire (CERQ), and the Hardiness Profile. Validity and reliability of the instruments were confirmed. Data analysis involved SPSS v25 and SmartPLS software for path analysis and hypothesis testing.Findings: Results indicated that negative cognitive emotion regulation strategies positively predicted engagement in high-risk sexual behaviors (β = 0.736) and negatively predicted psychological hardiness (β = –0.742). Conversely, positive regulation strategies were associated with decreased risky sexual behaviors (β = –0.738) and increased hardiness (β = 0.744). Psychological hardiness negatively predicted risky sexual behaviors (β = –0.748) and mediated the relationships between both positive and negative regulation strategies and risky behaviors. All hypothesized paths were statistically significant at p < 0.01, with model fit indices supporting the structural model’s adequacy.Conclusion: The study confirms the significant direct and indirect roles of cognitive emotion regulation strategies in predicting high-risk sexual behaviors among female adolescents, with psychological hardiness serving as a key mediating protective factor. These findings highlight the importance of fostering adaptive emotion regulation and resilience in interventions aimed at reducing sexual risk-taking in adolescent girls.